Takhrij and Syarah Hadith of Chemistry: Water and Fire as the Sustainer of Life - Abdul Latief Salim Azpar; Wahyudin Darmalaksana; R. Yuli Ahmad Hambali; Gina Giftia Azmiana Delilah (Gunung Djati Conference Series, 2021)
The purpose of this study is to discuss the hadith of the Prophet Muhammad ï·º about how water and fire became the basis of the change of civilization. This research method is qualitative through the approach of takhrij and syarah hadith with the analysis of energy materials. The results and discussion of this research are to prove that the Prophet Muhammad ï·º once said that humans will be connected to water and fire, and evidenced by the presence of hydroelectric power plants which are the largest suppliers in the manufacture of electrical energy for life. This research concludes that the hadith about water and fire is of poor quality according to the takhrij of the hadith, but this hadith has a lot of support from other hadiths of authentic quality and the hadith syarah explains the basics of water and fire for the continuity of life.